Strain Identification of Spodoptera frugiperda (J. E. Smith) from Serian and Kota Samarahan, Sarawak - Kueh, Chen Wah (Universiti Malaysia Sarawak, (UNIMAS), 2022)
Spodoptera frugiperda (J. E. Smith) is one of the most invasive pests around the world which brings huge economic lost to corn and rice farmers. In September 2019, Department of Agriculture, Sarawak has confirmed the existence of S. frugiperda in corn plantation of Kuching, Sarawak. The S. frugiperda is a polyphagous species with two major strains; corn strain and rice strain. Here, we tried to identify the strain of S. frugiperda from Serian and Kota Samarahan, Sarawak based on mitochondrial Cytochrome oxidase subunit 1 (CO1) gene marker and determine the genetic diversity with selected 144 CO1 gene sequences on GenBank database from Asia, Africa and North America continents. The results revealed that population of S. frugiperda had expand in all continents. Meanwhile, we have found rice strain in Sarawak, Malaysia. Based on migration pattern, only corn strain migrated to Asian countries, thus we proposed the presence of interstrain hybrid in corn plantation of Sarawak. Our study finds out that CO1 gene alone is ineffective to identify the strain of S. frugiperda, further study should involve the nuclear sex-linked triosephosphate isomerase gene for strain identification of S. frugiperda.